Applications of Plant Metabolic Engineering - Verpoorte, R.; Alfermann, A.W; Johnson, T.S (Springer Netherlands : Imprint: Springer, 2007)
Written by leading international experts in the field of plant metabolic engineering, this book discusses, mainly, applications of plant metabolic engineering. Metabolic engineering, which is part of second generation biotechnology, has made several contributions at basic level as well as at conceptualising products ever since its emergence in the early 1980s. Applications resulting from metabolic engineering are expected to play a very important role in future for plant breeding, e.g. for improved resistance or improved traits concerning health promoting constituents, and production of fine chemicals such as medicines, flavors and fragrances. Considering the tremendous progress that has been made since our first book in the year 2000 urgency was felt to bring together cutting edge research in plant metabolic engineering in applied aspects as a handy reference book. This book has been predominantly dedicated to applied research of metabolic engineering, and a part of it has been allotted for fundamental research that has potential applications. This book is a unique source of information for all those involved with plants as chemical factories of fine chemicals and also to more experienced scientists who work on transgenic plants, besides, senior researchers, graduate students, post-doctroral students, teachers and students as well.